Metodologia de projeto de um inversor ressonante auto-oscilante operando em alta frequência para aplicações a LED. - Rosa, William Guidolin da (2019)
In this dissertation, a design methodology is proposed for the Self Oscillating Resonant Converter operating in high frequency for LED lighting aplications. The high-frequency operation of electronic circuits has, as the most noticeable advantage, the reduction of weight and volume of the reactive elements in the system, such as capacitors and inductors, which imply miniaturization, increasing the power density of the prototypes. However, high-frequency operation makes the system susceptible to the effects of parasitic elements, such as the switching semiconductors terminal capacitances and its effects. In order to account for such parasitic elements, the classic design methodologies of the Self Oscillating Resonant Converter are revised, where there is no concern regarding the non-linearity of switching elements. After this revision, an analysis is made of the subsequent methodologies that appear from the new trend of frequency increase, and their considerations about parasitic elements. Finally, the proposed design methodology is presented for the Self Oscillating Resonant Converter operating in high frequency for LED applications. In the proposed design methodology, contributions made by previous methodologies are taken into account, and also new observations about the frequency increase are proposed, resulting in a design methodology that articulates considerations from the classic methodologies with the ones proposed from the current problematic.